Pengembangan Kawasan Rumah Pangan Lestari dengan Sistem Irigasi Tetes sebagai Upaya Peningkatan Ketahanan Pangan masyarakat pedesaan Kabupaten Banyuwangi - Effendi, Mokhtar; Ali Mudhor , Mohammad; Wahyu Wicaksono, Driyanto; Agustyaningsih, Rika; Hidayatullah, Arif (Universitas Mataram, 2025)
Food security remains a strategic national issue, particularly in rural areas that face challenges such as limited land, water availability, and technical skills in crop cultivation. Banyuwangi Regency has great agricultural potential; however, household yards are not yet optimally utilized. This community service program aimed to develop Sustainable Home Food Gardens (Kawasan Rumah Pangan Lestari/KRPL) through the application of drip irrigation systems as an effort to improve food security in Pengatigan Village, Rogojampi District, Banyuwangi. The program was carried out from July 2024 to February 2025, involving 20 participants from the PKK women’s group and youth organization (karang taruna). The methods employed were participatory approaches, including socialization, training, field demonstrations, and direct assistance. The results showed that the utilization of home yards through KRPL increased household food availability, reduced expenses, and opened opportunities for yard-based household businesses. The implementation of drip irrigation improved water use efficiency by 30–40% and supported better crop growth. Furthermore, the program strengthened social aspects through active community involvement and introduced small-scale entrepreneurship based on household yards. Therefore, the development of KRPL with drip irrigation systems can be an effective strategy to enhance food security and empower rural communities sustainably.